Pengaruh Modal Usaha dan Strategi Pemasaran terhadap Volume Penjualan pada Pelaku UMKM Mitra Mandiri Brebes - Slamet Bambang Riono; Moh. Nurizki; Dumadi Dumadi; Muhammad Syaifulloh; Hendri Sucipto (Fakultas Ekonomi Universitas Panca Marga, 2023)
Abstract The sales volume of MSME players in the Mitra Mandiri group is declining. Sales volume is one of the determining factors that greatly affects the achievement of net profit, while profit or profit is an important means for the survival of a business. This research uses a quantitative approach with explanatory research through associative research. Data were obtained using a) primary documents in the form of questionnaire answers from respondents, b) literature studies derived from several literature and other supporting readings. The results of this study found the value of the correlation coefficient of R Square of 0.637 and the value of the double coefficient of determination R2 = 0.798 and adjusted R Square of 0.630. The coefficient of determination of 0.637 states the amount of contribution of business capital (X1) and marketing strategy (X2) of 63.70% to the sales volume (Y) of MSME players of Mitra Mandiri Brebes. The correlation coefficient of 0.637 states the simultaneous influence of independent variables of business capital and marketing strategies on dependent variables of sales volume. Based on the regression equation 27.745 + 0.231 X1 + 0.451 X2. it can be interpreted that each increase in the units of the business capital variable (X1) and marketing strategy (X2) will increase the variable sales volume by 0.231 units of working capital, plus 0.451 units of marketing strategy, at a constant of 27.745. Keywords: Business Capital, Marketing Strategy, Sales Volume